ENGAGEMENT MODEL OF DOWNHOLE MOTOR AND APPLICATION - KUANG YuChun; ZHANG Cong; WU LongMei; DONG ZongZheng; REN HaiTao (Jixie qiangdu)
The interference between the rotor and stator has significant effect on the seal and mechanical performance of mudmotor. The suitable interference is significant to improve the performance of downhole motor. Based on the Hertz contact theory,the two-dimensional engagement model of rotor and stator was established. Through the balance theory of contact force system and the iteration method,the center trace of rotor and the normal interference were obtained. The profiles of rotor and stator were acquired through the measurement of two mudmotors which have different theoretical interference,and the calculated interferences were gained through the engagement model of mudmotor. Compared with the theoretical interference,the results show that the calculated interference values are a little larger. Meanwhile,two mudmotors‘ performance tests were conducted and the calculated interference can be more reasonable to explain the motor’s performance compared with the test data. Besides,when the calculated interference was in a range of suitable value,the downhole motor would have good performance.